Ranunculus kangmaensis (Ranunculaceae), a new synonym of Halerpestes tricuspis var. variifolia - Zhang, Meng; Zeng, You-Pai; Yang, Qin-Er (Phytotaxa, 2020)
Ranunculus kangmaensis (Ranunculaceae) was recently described from Kangmar (= Kangma) in Xizang (Tibet), China. Based on critical observations on herbarium specimens and living plants in the wild, together with evidence from achene surface morphology and karyology, we demonstrate that it does not belong to the genus Ranunculus but is identical with Halerpestes tricuspis var. variifolia. We therefore place R. kangmaensis in synonymy with H. tricuspis var. variifolia herein.